Effects of CoCl(2) on multi-lineage differentiation of C3H/10T1/2 mesenchymal stem cells - Yoo, Hong Il (Korean J Physiol Pharmacol, 2016)
Mesenchymal stem cells (MSCs) in the bone marrow and other somatic tissues reside in an environment with relative low oxygen tension. Cobalt chloride (CoCl(2)) can mimic hypoxic conditions through transcriptional changes of some genes including hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF). This study evaluated the potential role of CoCl(2) preconditioning on multi-lineage differentiation of C3H/10T1/2, a murine MSC line to understand its possible molecular mechanisms in vitro. CoCl(2) treatment of MSCs markedly increased HIF-1α and VEGF mRNA, and protein expression of HIF-1α. Temporary preconditioning of MSCs with CoCl(2) induced up-regulation of osteogenic markers including alkaline phosphatase, osteocalcin, and type I collagen during osteogenic differentiation, followed by enhanced mineralization. CoCl(2) also increased chondrogenic markers including aggrecan, sox9, and type II collagen, and promoted chondrocyte differentiation. CoCl(2) suppressed the expression of adipogenic markers including PPARγ, aP2, and C/EBPα, and inhibited adipogenesis. Temporary preconditioning with CoCl(2) could affect the multi-lineage differentiation of MSCs.